Effect of multivitamin drug on intractable dry eye symptoms - Park, Se Hie; Hwang, Jin Sun; Shin, Young Joo (Frontiers in Medicine, 2022)
Dry eye is a disorder of tear film and ocular surface characterized by ocular discomforts. It is associated with multiple causes and sometimes intractable. We investigated the effect of oral multivitamin supplementation (MVG) on dry eyes. Tear break-up time (TBUT), fluorescein ocular surface staining score, and tear secretion Schirmer test were measured in dry eye patients refractory to conventional topical treatment. The ocular surface disease index (OSDI), visual analog pain score (VAS), and modified standardized patient evaluation of eye dryness questionnaire were analyzed. In total, 42 eyes of 42 patients were included. TBUT increased at 1 and 3 months compared to baseline (p < 0.05). OSDI decreased at 1 and 3 months compared to baseline (p < 0.05). VAS score, impact on life, and frequency of total symptoms decreased at 3 months compared to baseline (p < 0.05). Oral administration of MVG, a vitamin complex formulation, was effective in stabilizing tear stability and alleviating symptoms in patients with intractable dry eye. Thus, it may be a viable treatment option for intractable dry eye.